Quality of internet information to aid patient decision making in locally advanced and recurrent rectal cancer. Issue 6 (December 2022) - Williams, A.; Cunningham, A.; Hutchings, H.; Harris, D.A.; Evans, M.D.; Harji, D.
Abstract: Background: To review whether online decision aids are available for patients contemplating pelvic exenteration (PE) for locally advanced and recurrent rectal cancer (LARC and LRRC). Methods: A grey literature review was carried out using the Google Search™ engine undertaken using a predefined search strategy (PROSPERO database CRD42019122933). Written health information was assessed using the DISCERN criteria and International Patient Decision Aids Standards (IPDAS) with readability content assessed using the Flesch-Kincaid reading ease test and Flesch-Kincaid grade level score. Results: Google search yielded 27, 782, 200 results for the predefined search criteria. 131 sources were screened resulting in the analysis of 6 sources. No sources were identified as a decision aid according to the IPDAS criteria. All sources provided an acceptable quality of written health information, scoring a global score of 3 for the DISCERN written assessment. The median Flesch-Kincaid reading ease was 50.85 (32.5–80.8) equating to a reading age of 15–18 years and the median Flesch-Kincaid grade level score was 7.65 (range 3–9.7), which equates to a reading age of 13–14. Conclusions: This study has found that there is a paucity of online information for patients contemplating PE. Sources that are available are aimed at a high health literate patient. Given the considerable morbidity associated with PE surgery there is a need for high quality relevant information in this area. A PDA should be developed to improve decision making and ultimately improve patient experience. Highlights: There are no developed decision aids for pelvic exenteration The online resources available for pelvic exenteration are inadequate Readability of online resources for pelvic exenteration fails recommendations Patient level information is required for patients undergoing complex pelvic surgery